2021
DOI: 10.1016/j.tins.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Roles of KCC2 in Cortical Development

Abstract: KCC2, best known as the neuron-specific chloride-extruder that sets the strength and polarity of GABAergic currents during neuronal maturation, is a multifunctional molecule that can regulate cytoskeletal dynamics via its C-terminal domain (CTD). We describe the molecular and cellular mechanisms involved in the multiple functions of KCC2 and its splice variants, ranging from developmental apoptosis and the control of early network events to the formation and plasticity of cortical dendritic spines. The versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 155 publications
(284 reference statements)
3
66
0
Order By: Relevance
“…Tang et al (2016) have shown that KCC2 is a target of Mecp2 and that compounds enhancing the expression of KCC2 rescued the morpho-functional abnormalities of human RTT neurons and exerted therapeutic effects in early symptomatic Mecp2 −/y mice (Tang et al, 2019). Based on our study, this therapeutic action may be accounted for by a rescue of chloride homeostasis in non-hippocampal brain regions or, alternatively, mediated through interactions with a wide range of cytoskeleton-associated and/or membrane proteins, independent of its Cl − transport function (Virtanen et al, 2021), as reported for the regulatory role of KCC2 on spines formation (Li et al, 2007), synaptic plasticity (Gauvain et al, 2011;Chevy et al, 2015), and neuronal excitability (Goutierre et al, 2019). Examination of chloride homeostasis in additional brain regions at symptomatic stages would be interesting to address these points.…”
Section: Discussionmentioning
confidence: 60%
“…Tang et al (2016) have shown that KCC2 is a target of Mecp2 and that compounds enhancing the expression of KCC2 rescued the morpho-functional abnormalities of human RTT neurons and exerted therapeutic effects in early symptomatic Mecp2 −/y mice (Tang et al, 2019). Based on our study, this therapeutic action may be accounted for by a rescue of chloride homeostasis in non-hippocampal brain regions or, alternatively, mediated through interactions with a wide range of cytoskeleton-associated and/or membrane proteins, independent of its Cl − transport function (Virtanen et al, 2021), as reported for the regulatory role of KCC2 on spines formation (Li et al, 2007), synaptic plasticity (Gauvain et al, 2011;Chevy et al, 2015), and neuronal excitability (Goutierre et al, 2019). Examination of chloride homeostasis in additional brain regions at symptomatic stages would be interesting to address these points.…”
Section: Discussionmentioning
confidence: 60%
“…Without KCC2, dendritic spine morphology is compromised, producing stubby structures that compromise the function of excitatory synapses (Li et al, 2007). Indeed, with the broad functions (independent of ion transport) of KCC2, it's no surprise that reduced GABAergic inhibition is not the only phenotype in KCC2-related pathologies and may contribute to other symptoms in HD (Tang, 2020;Virtanen et al, 2021).…”
Section: Expression and Functionmentioning
confidence: 99%
“…In vivo reports (Kirmse et al, 2015 ; Murata and Colonnese, 2020 ) and modeling studies (Lombardi et al, 2021 ) provide a more complex picture of the developmental shift in GABA action, especially when on-going spatiotemporal interactions between GABAergic and glutamatergic inputs are taken into account (for review Kilb, 2021 ). It is not the aim of this short review to summarize the current data on this topic, but it is well-accepted that the intracellular chloride concentration is regulated by development, various molecular factors, and neuronal activity (Kaila et al, 2014 ; Watanabe and Fukuda, 2015 ; Virtanen et al, 2020 , 2021 ). Thus, the action and function of the important neurotransmitter GABA, and also glycine and taurine (for review Kilb and Fukuda, 2017 ), changes dramatically during the first postnatal week in rodent cortex!…”
Section: The Challenges Of Studying the Neurophysiology Of The Developing Cerebral Cortex In Rodentsmentioning
confidence: 99%